1996
DOI: 10.2307/3283798
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Neospora caninum and Toxoplasma gondii Antibodies in Coyotes (Canis latrans) and Experimental Infections of Coyotes with Neospora caninum

Abstract: Antibodies to Neospora caninum were detected in 5 (10%) of 52 coyotes from Texas. Antibodies to Toxoplasma gondii were detected in 32 (62%) of 52 samples from these same coyotes. Four (80%) of the 5 coyotes that were seropositive for N. caninum also had antibodies to T. gondii. Nineteen (37%) of the coyotes did not have antibodies to either parasite. Three coyote pups were inoculated with the brains from mice infected with 3 strains of N. caninum originally isolated from dogs. None of the pups developed neospo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
25
1
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(29 citation statements)
references
References 9 publications
1
25
1
2
Order By: Relevance
“…A difference in foraging patterns is an inadequate explanation for the finding that blacktailed deer sera in this project were negative for both N. caninum antibodies and T. gondii. Carnivores, in addition to being infected by ingesting oocysts, can potentially become infected and develop antibodies to T. gondii and N. caninum by consuming meat containing bradyzooites (Dubey, 1982(Dubey, , 1983Lindsay et al, 1996;Gondim et al, 2005). This increased risk compared to noncarnivores alters the expected antibody prevalence of N. caninum and T. gondii in carnivores compared to the herbivores that they consume.…”
Section: Discussionmentioning
confidence: 99%
“…A difference in foraging patterns is an inadequate explanation for the finding that blacktailed deer sera in this project were negative for both N. caninum antibodies and T. gondii. Carnivores, in addition to being infected by ingesting oocysts, can potentially become infected and develop antibodies to T. gondii and N. caninum by consuming meat containing bradyzooites (Dubey, 1982(Dubey, , 1983Lindsay et al, 1996;Gondim et al, 2005). This increased risk compared to noncarnivores alters the expected antibody prevalence of N. caninum and T. gondii in carnivores compared to the herbivores that they consume.…”
Section: Discussionmentioning
confidence: 99%
“…Besides dogs, other canids have been considered to be potential definitive hosts of N. caninum (McAllister, 1999). Antibodies to N. caninum have been found in North American coyotes (Canis latrans), British red foxes (Vulpes vulpes), and Australian dingoes (Canis familiaris dingo; Lindsay et al, 1996;Barber et al, 1997;Buxton et al, 1997). In Texas, Barling et al (2000) performed a spatial analysis study and found statistical associations among the density of cattle, seropositivity for N. caninum, and abundance of coyotes and grey foxes (Urocyon cinereoargenteus).…”
mentioning
confidence: 99%
“…For example, does infection with one parasite prevent infection with the other or is the outcome of infection influenced by co-infection ? Previous serological investigations have shown that antibodies to both parasites were present in several species including coyotes (Lindsay et al 1996) and non-domestic felids from southern Africa (Cheadle, Spencer and Blagburn, 1999) but few studies have investigated this question in other species. Previous in vitro studies (Sunderman and Estridge, 1999) have demonstrated that Toxoplasma and Neospora can co-exist in tissue culture, and both species could invade the same host cell and undergo endodyogeny.…”
mentioning
confidence: 99%